2017
DOI: 10.1002/jcb.25809
|View full text |Cite
|
Sign up to set email alerts
|

2‐Methoxyestradiol‐Mediated Induction of Frzb Contributes to Cell Death and Autophagy in MG63 Osteosarcoma Cells

Abstract: Osteosarcoma is a bone tumor that mainly affects children and adolescents. Although its pathogenesis is still not fully understood, activation of Wnt signaling has been implicated in the development and metastasis of osteosarcoma. In this report, we have investigated the effect of the anti-tumor compound, 2-methoxyestradiol (2-ME) on Wnt antagonist frizzled-related protein b (Frzb), also known as secreted frizzled-related protein (sFRP)3 in human osteosarcoma (MG63) cells. Our results show that 2-ME treatment … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 48 publications
0
16
0
Order By: Relevance
“…Herein, we observed that the induction of autophagy by 2-ME was strictly correlated with the inhibition of proliferation and migration and the induction of apoptosis in osteosarcoma cells. The correlation of the induction of autophagy by 2-ME with the induction of cell death has previously been demonstrated in various experimental models including osteosarcoma cells (60,61). Moreover, it has been suggested the molecular crosstalk between 2-ME-induced apoptosis and autophagy is associated with its impact on microtubule integrity in cervical adenocarcinoma cells (62).…”
Section: Discussionmentioning
confidence: 90%
“…Herein, we observed that the induction of autophagy by 2-ME was strictly correlated with the inhibition of proliferation and migration and the induction of apoptosis in osteosarcoma cells. The correlation of the induction of autophagy by 2-ME with the induction of cell death has previously been demonstrated in various experimental models including osteosarcoma cells (60,61). Moreover, it has been suggested the molecular crosstalk between 2-ME-induced apoptosis and autophagy is associated with its impact on microtubule integrity in cervical adenocarcinoma cells (62).…”
Section: Discussionmentioning
confidence: 90%
“…Human multidrug-resistant cell line U2OSR is a kind gift from Dr. Zhenfeng Duan’s laboratory (University of California, Los Angeles, CA, USA). Cells were cultured in DMEM/F12 medium and maintained at 37 °C [ 16 , 17 ].…”
Section: Methodsmentioning
confidence: 99%
“…Cell lysis and preparation of cytoplasmic protein extract were carried out as described by 2 reports [ 16 , 19 ]. Briefly, cells were resuspended with lysis buffer (0.15 M NaCl, 5 mM EDTA, 10 mM Tris-Cl, 1% Triton X-100), and protein concentrations were determined by Bradford assay.…”
Section: Methodsmentioning
confidence: 99%
“…Moreover, autophagy and apoptosis induced by 2-ME were decreased by FRZB/sFRP3 siRNA. Altogether, this suggested the potential use of FRZB/sFRP3 in osteosarcoma [83]. In 2018, the same team analyzed the sera of 67 osteosarcoma and age-matched nondisease controls and observed that the level of FRZB/sFRP3 was lower in osteosarcoma samples.…”
Section: Using Sfrps In Cancer Therapy?mentioning
confidence: 97%